SUBSTITUTION OF PLANT UTILIZATION ON THE FOREST GARDENS OF MAIBRAT, WEST PAPUA - Susan Salosa (Pusbindiklat - LIPI, 2011)
The dividing in many provinces in Indonesia including West Papua has affected those areas in mobilization of information within areas, infrastructure changing such as roads, bridges, buildings and ofﬁ ces. Migration of people is also contributed to local plants existing and appearing of invasive species in the community gardens. The local plants are becoming scarce and ﬁ nally disappeared. The research was conducted by ﬁ eld survey technique on three villages: Arne, Framu, and Sembaro in the district of South Sorong (recently become part of Maibrat district). Data were analyzed tabulation continued with SPSS and diversity index. The research shows that aboutnine spesies, seven are species of bete and two kinds of pumpkin, become extinct. On the other hand peanut andred onion become part of local community’s life.